2015
DOI: 10.1002/jsfa.7257
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic variation of bioactive compounds and aflatoxins in contaminated Radix Astragali during extraction process

Abstract: This investigation would benefit from the determination of the dynamic variation of aflatoxins in infected herbs in preparation treatments, in order to further develop aflatoxin limits in herbal preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Too many uncontrollable factors affect the quality of products, like mold pollution, unstable quality, long time consuming, etc. For example, Hu et al (2016) found that the storage surrounding the condition of CRP was suitable for A. flavus growing of traditional natural aging. Thus, effectively accelerating aging technologies for tangerine peel are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Too many uncontrollable factors affect the quality of products, like mold pollution, unstable quality, long time consuming, etc. For example, Hu et al (2016) found that the storage surrounding the condition of CRP was suitable for A. flavus growing of traditional natural aging. Thus, effectively accelerating aging technologies for tangerine peel are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The general rule requires that the common determination method of common mycotoxins is ultra high performance liquid chromatography tandem mass spectrometry [ 14 , 15 ]. However, in the production, harvest, storage, treatment and processing of TCMs, due to the limited external environment and production process, it is inevitable to introduce exogenous mycotoxins into the treatment process [ 16 ].…”
Section: Introductionmentioning
confidence: 99%